2015
DOI: 10.5114/pdia.2014.40965
|View full text |Cite
|
Sign up to set email alerts
|

21-year retrospective study of the prevalence of Scopulariopsis brevicaulis in patients suspected of superficial mycoses

Abstract: IntroductionIn the genus Scopulariopsis, Scopulariopsis brevicaulis is the most common aetiological agent of infections in humans. It usually affects nails and is one of the commonest moulds associated with onychomycoses. Other forms of infections (skin, subcutaneous, deep tissues, and disseminated infections) have also been described.AimTo examine the prevalence of S. brevicaulis in clinical materials obtained from patients suspected of keratinized tissues mycoses.Material and methodsThe analysis of the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…Although S. brevicaulis is a mold of the Microascus genus, it was grouped into one of the main clades of the MSP-dendrogram and not as a real outgroup. S. brevicaulis is regularly isolated from nail infections and, hence, typically associated with mold-related onychomycosis; keratinolytic activities are well reported ( Issakainen et al., 2007 ; Macura and Skóra, 2015 ). Although the majority of the extracted proteins for MALDI-TOF MS are ribosomal proteins rather than secreted proteases, this similar lifestyle compared to dermatophytes may explain the position of S. brevicaulis in the dendrogram.…”
Section: Discussionmentioning
confidence: 99%
“…Although S. brevicaulis is a mold of the Microascus genus, it was grouped into one of the main clades of the MSP-dendrogram and not as a real outgroup. S. brevicaulis is regularly isolated from nail infections and, hence, typically associated with mold-related onychomycosis; keratinolytic activities are well reported ( Issakainen et al., 2007 ; Macura and Skóra, 2015 ). Although the majority of the extracted proteins for MALDI-TOF MS are ribosomal proteins rather than secreted proteases, this similar lifestyle compared to dermatophytes may explain the position of S. brevicaulis in the dendrogram.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, Scapulariopsis spp. are mainly associated with superficial infections of keratinized tissues, but they are also causative agents of cutaneous, subcutaneous, and deep-tissue infections and disseminated infections [66].…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…Since Scopulariopsis spp. are known to be keratinophilic, S. bravicaulis has proven to be one of the predominant species among non-dermatophytic filamentous fungi in onychomycoses [66]. A retrospective analysis in the Croatian population showed that S. brevicaulis was isolated from nail, skin, and scalp scrapings, and most of the patients from whom the specimens were obtained lived in rural settings, working as farmers in close contact with the soil and domestic animals.…”
Section: Onychomycosismentioning
confidence: 99%
“…Na uwagę zasługuje fakt, że po raz pierwszy potwierdzono metodami molekularnymi, że czynnikiem etiologicznym onychomykozy mogą być grzyby pleśniowe, takie jak Fusarium spp., Acremonium spp., Aspergillus spp. i Scopulariopsis spp., które dotychczas nie były dostrzegane i uważane za kontaminację próbek dermatologicznych przesyłanych do laboratorium [37,46,50].…”
Section: Zalety I Wady Molekularnych Metod Identyfikacyjnych Stosowanunclassified